Learning curve analysis of transurethral thulium fiber laser enucleation of the prostate with preserving urethral Mucosa at the prostatic apex - Xie, Dawei; Wei, Yirui; He, Weifeng; Wang, Hao; Yang, Pushen; Wu, Liyang; Wang, Jianwen (Frontiers in Surgery, 2025)
ObjectiveTo introduce a unique surgical technique, analyze perioperative data to demonstrate the safety of Thulium Fiber Laser Enucleation of the Prostate (ThuFLEP) with preservation of the urethral mucosa at the prostatic apex, and construct a learning curve to assess its feasibility and potential for broader clinical application is the aim of this study.MethodsFrom June 2020 to June 2024, a urologist at Beijing Chaoyang Hospital, with no prior ThuFLEP experience, was trained under the supervision of an experienced chief physician. A retrospective analysis of 100 Benign Prostatic Hyperplasia (BPH) patients treated with ThuFLEP was conducted. Perioperative data were analyzed, including prostate volume, operative time, and enucleation weight. Statistical methods included T-tests, chi-square tests, and linear regression. Learning curves were constructed using Loess regression, with box plots visualizing differences in operative time, efficiency, and enucleation ratio efficacy. Postoperative follow-up assessed changes in IPSS, Qmax, and urinary incontinence.ResultsThe learning curve analysis showed a significant reduction in operative time after 56 cases. Linear regression indicated a decrease in operative time (R = −0.5, p < 0.01) and improvements in efficiency (R = 0.14, p < 0.01) and enucleation ratio efficacy (R = 0.41, p < 0.01) with increased experience. Comparing the first and last 50 cases, operative time and enucleation efficiency significantly improved (p < 0.01). Postoperatively, 31% of patients experienced incontinence one week after catheter removal, but all recovered within 12 weeks. IPSS scores improved by 13.67 ± 3.99 points.ConclusionsThuFLEP with urethral mucosa preservation improves efficiency, reduces operative time, and has a manageable learning curve. Attention to complications and structured mentorship are crucial for successful implementation.